Liturgical theology after Schmemann : an orthodox reading of Paul Ricoeur - Butcher, Brian A. (Orthodox Christianity and contemporary thought., 2018)
French philosopher Paul Ricoeur gave sustained attention to several themes pertinent to a hermeneutics of liturgy, including symbol, metaphor, narrative, subjectivity and memory. This book explores how Ricoeur's original insights may serve to renew contemporary Orthodox liturgical theology. The Byzantine-Rite ""Great Blessing of Water"" serves as a case study